A cidade educadora e o enfoque CTS : articulações possíveis a partir dos professores de ciências em formação - Fabrício, Tárcio Minto (2016)
The Science, Technology and Society (STS) approach to Science Education and the Educating Cities conceptual framework share different aspects that allow their identification as progressive educational ideas. Aiming to understand which relationships future teachers establish with these educational approaches, we arrive at our research question: how do teachers in training understand the possibilities to teach and learn science considering both frameworks and their interactions? Faced with this question, our goal was to contribute to a deeper understanding about the perception of future educators regarding the use of the STS and Educating Cities approaches. Therefore, our specific objectives were to identify and characterize the spaces that are recognized by teachers in training as educational spaces, aiming to understand the meanings assigned to such spaces; identify the extent to which references to the STS and Educating Cities approaches occur with respect to their teaching practices, identifying conceptions of teaching and learning science presented by the future teachers, as well as meanings assigned to the use of cities as an educational possibility; observe to what extent the STS and Educating Cities approaches are seen as possibilities regarding their future teaching careers, as well as the obstacles they identify concerning these possibilities. Pursuing these objectives, we have analyzed textual documents produced by students engaged in the licenciate degree course of Biological Sciences at the Federal University of São Carlos who attended the discipline “Practices and Research in Biological Sciences Teaching III," offered in the second half of 2014, using discursive textual analysis. The results reveal lack of familiarity of most students in relation to these approaches and reinforce the need for a stronger incorporation of the STS and Educating Cities perspectives in curriculum guidelines both for Basic Education as for the universities themselves and the importance of adopting these perspectives in teacher education.